Validity of the Youth Psychopathic Traits Inventory–Short Version in Justice-Involved and At-Risk Adolescents. (April 2019) - Gillen, Christopher T. A.; MacDougall, Emily A. M.; Forth, Adelle E.; Barry, Christopher T.; Salekin, Randall T.
The current study examined the reliability and validity of the Youth Psychopathic Traits Inventory–Short Version (YPI-S) in two different samples of at-risk adolescents enrolled in a residential program ( n = 160) and at a detention facility ( n = 60) in the United States. YPI-S scores displayed adequate internal consistency and were moderately associated with concurrent scales on other self-report psychopathy measures and externalizing behaviors. YPI-S scores were moderately related to interviewer-ratings of the construct using the four-factor model of the Psychopathy Checklist: Youth Version. Findings suggest that the YPI-S may be a clinically useful and valid tool for the assessment of psychopathic traits in juvenile settings. This may be particularly true given the differential predictive utility of each of its dimensions.